Meningkatkan Kemampuan Berhitung Melalui Metode Jarimatika di Panti Asuhan Washliyah Lubuk Pakam - Ikhwani Saufa; Husni Thamrin (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2022)
Mathematics is one of the main subjects at every level of education that applies not only in Indonesia but also at any level of education throughout the world. Mathematics has become a scary thing for most children so that it is one of the causes of unsatisfactory learning achievement in mathematics. Children at the Washliyah Orphanage Lubuk Pakam, North Sumatra also feel that mathematics is a scary subject. Therefore, one of the objectives of the Field Work Practice I is to provide assistance to clients so that they can improve their mathematical skills, namely counting. The process of providing assistance was also carried out in the Field Work Practice I mini project activity, using the case work method through the general or general intervention stage consisting of Engagement Intake Contract, Assessment, Planning, Intervention, Evaluation, and Termination. The process of solving client problems is to introduce the Jarimatika arithmetic method. The goal of the program is successful, because the client can solve the problem.